Chemical constituents from the leaves of Liriodendron chinense and their chemophenetic significance - Qiu-Ye Zhao; Qiu-Hua Wang; Xin-Ying Wang; Lu Sai; Shi-Huan Yin; Dai-Yi Liu; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

Generation of transgenic pigs with targeted insertion of a wildtype copy of human PKD2 gene - Xue-Lin Zhang; Jia-Ning Luo; Yue Cao; Jiu-Xiao Zhao; Yuan Zhang; Sai-Fei Xu; Le-Nan Zhuang; Jin He (Molecular Biology Reports, 2026)

A hypoxia-responsive migrasome-related lncRNA signature predicts prognosis and suggests the MSC-AS1/ITGA5 axis as a potential therapeutic target in head and neck squamous cell carcinoma - Sai Liang; Xin Lin; Fubo Wang; Ming Yang; Gang Qin (Functional & Integrative Genomics, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

Hypurpurins A-P, furanolabdane diterpenoids from the aerial parts of Hypoestes purpurea and their bioactivities - Lin-Fen Ding; Bin Cheng; Mei-Yi Zhang; Shi-Huan Yin; Xin-Ying Wang; Lu Sai; Hui-ling Zhou; Xuan Jiang; Jia Su; Xing-De Wu (Phytochemistry, 2026)

Mechanism of surface-functionalized materials for efficient iodide removal: Performance and theoretical insights - Meng Ren; Xuedan Cui; Sai Yuan; Ying Yang; Xiaotian Xu; Pengjie Zhao; Tianda Pu; Guilan Duan; Yinjie Zhang; Aijun Lin (Journal of Environmental Chemical Engineering, 2026)

Chemical constituents from the leaves of Yulania denudata and their chemotaxonomic significance - Zhen-Quan Li; Qiu-Ye Zhao; Hui-Ling Zhou; Shi-Huan Yin; Xuan Jiang; Xin-Ying Wang; Lu Sai; Lin-Fen Ding; Liu-Dong Song (Biochemical Systematics and Ecology, 2026)

Dipole driven interfacial coupling in COF/Bi2Fe4O9 S-scheme heterojunctions greatly boosts PMS activation for neonicotinoids degradation - Sai Bai; Wenzhen Lu; Lin Yang; Congcong Duan; Zhixuan Wang; Yan Shao; Tianjiao Xia; Lingyan Zhu (Journal of Hazardous Materials, 2026)

Enhancement effect of myofibril proteins gel stability by alkaline electrolyzed water and bacterial cellulose: Insights from physicochemical and biochemical characterization - Yilin Lin; Siyun Xie; Sai Li; Jili Wang; Yacheng Hao; Yehui Zhang; Yigang Yu (Innovative Food Science & Emerging Technologies, 2026)

A novel endophytic Penicillium sp. JL76001 and its metabolite sclerotiorin: A multi-target and sustainable strategy for biocontrol of tomato Fusarium wilt - Xuecheng Sun; Yutong Feng; Pan Xiang; Fudong Wang; Weizhuo Tang; Sai Jiang; Meng Su; Zixian Zeng; Shunxiang Li; Lin Jiang (Pesticide Biochemistry and Physiology, 2026)

Surface nickel doping and boronization with island-sea effect for sustainable hydrodechlorination via a non-radical pathway - Wenjie Lin; Xinran Xiong; Wei Peng; Sai Yang; Junyue Ji; Zelong Zheng; You-an Chen; Yi-bo Hu (Journal of Environmental Chemical Engineering, 2026)

A sustained-release antibacterial gelatin hydrogel based on metal-phenolic networks for long-term preservation of prefabricated meat - Yanan Liu; Yuhao Huang; Qileng Aori; Yu Wang; Sai Zhao; Zhen-Lin Xu (Food Chemistry, 2026)

Targeting perivascular adipose tissue in vascular aging: innovative translational strategies for disease prevention and monitoring - Peng-Xin Wang; Sha-Qi He; Bei Huang; Zi-Fei Liu; Feng Xu; Jun-Jie Yang; Sai Lu; Hui-Xiang Chen; Ze-Qiang Cai; Ling-Qing Yuan; Xiao Lin (Apoptosis, 2026)

Enhanced adsorption of La(III) and Ce(III) onto phytic acid modified N-(2-hydroxyethyl) acrylamide - Zengjin Fu; Yan Hao; Tingrui Lin; Huiling Ma; Huazheng Sai; Hui Yang (Journal of Water Process Engineering, 2026)

African swine fever virus pNP419L inhibits host translation and increases viral replication through the PERK/eIF2α pathway - Xueying Wang; Zixuan Wang; Yilin Guo; Sai Niu; Rui Liang; Lin Cheng; Hakimeh Baghaei Daemi; Guiqing Peng (Veterinary Microbiology, 2026)

Glacial changes in the eastern Kunlun Mountains since the Little Ice Age - Sai Lin; Jinhua Liu; Yingkui Li; Haiping Hu; Changsheng Ye; Qiang Liu; Shunzi Pi (Quaternary International, 2026)

Improving stability and UV protection properties of phycocyanin nanoparticle-based Pickering emulgels via amorphous cationic starch complexation - Yacheng Hao; Jiahao Mei; Dongfang Ling; Zhe Zhang; Sai Li; Zhiyong Gong; Xin Liu; Mingfeng Xu; Yilin Lin; Rongrong Yu (Carbohydrate Polymers, 2025)

Early Carboniferous Magmatic Rocks in Eastern Myanmar: Implications for the Tethyan Evolution - San Win; Qinglai Feng; Ye Myint Swe; Tianyu Zhao; Zhengqin Gan; Xiaomei Nie; Aung Khaing; Sai Naing Lin Aung (Journal of Earth Science, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Dual modification of soy protein isolate by phlorotannins and enzymatic hydrolysis: Stability and digestive properties - Ziteng Lian; Ruihan Su; Qianqian Zhang; Yaqi Tang; Sai Yang; Xiuying Liu; Lin Cheng; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2025)

Biocontrol mechanism of a newly isolated Streptomyces sp. JL2001 against Ralstonia solanacearum via aerugine - Zixian Zeng; Wei Cao; Hong Pu; Dousheng Wu; Sai Jiang; Meng Su; Yajing Wang; Zhi Wang; Xin Zhao; Juan Li; Shunxiang Li; Lin Jiang (Pesticide Biochemistry and Physiology, 2025)

Occurrence, removal and ecological risk assessment of antibiotics in rural domestic wastewater treatment systems in the Beijing-Tianjin-Hebei region - Hongliang Wang; Sai Zhang; Ziyu Lin; Feifei Xiao; Bao Xiang; Ao Li (Journal of Hazardous Materials, 2025)

Pathogenic Ralstonia solanacearum in Agriculture: A Review of Prevention and Control Strategies Based on Natural Products - Lin Jiang; Zixian Zeng; Amanpreet Kaur; Wenlong Yang; Huaxue Huang; Shunxiang Li; Sai Jiang (Current Microbiology, 2025)

Advances in Research on Soil-Borne Diseases of Medicinal Plants and Their Prevention and Control - Linghe Huang; Yanxia Huang; Sai Jiang; Zixian Zeng; Zhaoyang Tan; Huaxue Huang; Zhi Wang; Shunxiang Li; Dousheng Wu; Lin Jiang (Current Microbiology, 2025)

Identification of Chlortetracycline Hydrochloride as a Antibacterial Compound Against Pseudomonas syringae pv. tomato DC3000 Through Natural Products Library Screening - Lin Jiang; Linghe Huang; Yajing Wang; Jing Li; Zixian Zeng; Wenlong Yang; Sai Jiang; Dousheng Wu; Zhi Wang; Shunxiang Li; Yanxia Huang; Hong Pu (Current Microbiology, 2025)

Influence of Surging and Pitching Behaviors on the Power Output and Wake Characteristics of a 15 MW Floating Wind Turbine - Tsung-Yueh Lin; Hoi-Yi Tong; Sai-Kiu Wong; Shiu-Wu Chau (Journal of Marine Science and Engineering, 2025)
This study investigates the impacts of surging and pitching motions on the power generation performance and wake characteristics of an IEA 15 MW offshore wind turbine under specific inflow wind conditions. The three-dimensional, unsteady continuity equation, momentum equations, and SST k–ω turbulence model are solved numerically using the computational fluid dynamics software STAR-CCM+ (version 2206) to simulate the aerodynamic flow field around the turbine rotor and in its downstream wake region. Under the condition of an inflow wind speed of 9 m/s at hub height and a corresponding rotor rotational speed of 7.457 RPM, the surging and pitching motions of the turbine are prescribed by sinusoidal functions with a period of 45 s and amplitudes of 2.75 m and 5°, respectively. This study analyzes and quantifies the power output and wake characteristics of the turbine over a duration corresponding to 200 rotor revolutions, considering stationary, surging, and pitching conditions. The results indicate that the surging and pitching motions of the turbine cause reductions in the mean power output of 2.18% and 3.54%, respectively, compared to a stationary condition. The surging and pitching motions also lead to significant wake enhancement in the downstream region, and a minimum spacing of downstream wind turbines is suggested.

Structural characteristics of global virtual water network driven by food consumption in the Belt and Road Initiative region - Qiumeng Zhong; Jiajing Pan; Zehan Lin; Yumeng Li; Xin Mo; Pan He; Xin Cao; Sai Liang (Resources, Conservation and Recycling, 2025)

Analytical solution for longitudinal equivalent bending stiffness of large-diameter shield tunnels with internal structures - Tao Chen; Huai-Na Wu; De-Sai Guo; Xin-Xin Yang; Hong-Zhan Cheng; Lin-Song Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Unraveling carbon mineralization patterns and mechanisms in conservation agriculture: A global synthesis and multi-point experiment - Cong He; Jin-Sai Chen; Shou-Wei Han; Wen-Sheng Liu; Wen-Xuan Liu; Olatunde Pelumi Oladele; Yash Pal Dang; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Journal of Cleaner Production, 2025)

Strategies for crop straw management in China's major grain regions: Yield-driven conditions and factors influencing the effectiveness of straw return - Jia Cheng; Bai-Jian Lin; Jin-Sai Chen; Hong-Xuan Duan; Yuan-Feng Sun; Xin Zhao; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2025)

CircHAT1 regulates the proliferation and phenotype switch of vascular smooth muscle cells in lower extremity arteriosclerosis obliterans through targeting SFRS1 - Xian-ying Huang; Fang-yong Fu; Kai Qian; Qiao-li Feng; Sai Cao; Wei-yu Wu; Yuan-lin Luo; Wei-jie Chen; Zhi Zhang; Shui-chuan Huang (Molecular and Cellular Biochemistry, 2025)

Nature-inspired temperature-adaptive module: Achieving all-season passive thermal regulation for buildings - Lin Liang; Jianheng Chen; Kaixin Lin; Xueming Yang; Sai Liu; Chui Ting Kwok; Hao Pan; Ziai Liu; Aiqiang Pan; Siru Chen; Yihao Zhu; Wei Li; et al. (Energy and Buildings, 2024)

Analysis of chemosensitivity of tumor spheroids exposed to two-dimensional gradient of combination drugs in a hydrogel-based diffusion microfluidic platform - Kin Fong Lei; Yu-Ting Lin; Sai Kiran Reddy Boreddy; Ping-Ching Pai (Analytica Chimica Acta, 2024)

Alendronate sodium induces G1 phase arrest and apoptosis in human umbilical vein endothelial cells by inhibiting ROS-mediated ERK1/2 signaling - Yi Feng; Shao-Qin Tu; Yu-Luan Hou; Yi-Ting Shao; Lin Chen; Zhi-Hui Mai; Yu-Xuan Wang; Jia-Ming Wei; Sai Zhang; Hong Ai; Zheng Chen (Toxicology, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Genomic Investigation of a Rhizosphere Isolate, Streptomyces sp. JL1001, Associated with Polygonatum cyrtonema Hua - Lin Jiang; Zixian Zeng; Zhi Wang; Min Tang; Sai Jiang; Qingxian Ma; Zhong Wang; Dian Peng; Shunxiang Li; Hong Pu (Current Microbiology, 2024)

Relevance of genetic causes and environmental adaptation of Cronobacter spp. isolated from infant and follow-up formula production factories and retailed products in China: A 7-year period of continuous surveillance based on genome-wide analysis - Wei Tong; Dajin Yang; Shaofu Qiu; Sai Tian; Zehong Ye; Shuran Yang; Lin Yan; Weiwei Li; Ning Li; Xiaoyan Pei; Zhongqing Sun; Chengwei Liu; et al. (Science of The Total Environment, 2024)

Emamectin benzoate-induced toxicity affects intestinal epithelial integrity involving apoptosis - Xingyu Yue; Fengxiang Lin; Shuyan Gui; Sai Zhang; Zongbin Wu; Yuxin Xiang; Tianxiang Xiao; Jinjing Xiao; Haiqun Cao; Yanhong Shi (Food and Chemical Toxicology, 2024)

Examining the impact of common faults on chiller performance through experimental investigation and parameter sensitivity analysis - Zhanwei Wang; Penghua Xia; Sai Zhou; Lin Wang; Jingjing Guo; Xiuzhen Li; Jingfeng Shi; Jianxing Chen (Energy and Buildings, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

Insight into succinylated modified soy protein isolate-sodium alginate emulsion gels: Structural properties, interactions and quercetin release behavior - Sai Yang; Ziteng Lian; Lin Cheng; Xiuying Liu; Shicheng Dai; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2024)

Inhalation bioaccessibility of imidacloprid in particulate matter: Implications for risk assessment during spraying - Yuying Liu; Fengxiang Lin; Xingyu Yue; Sai Zhang; Han Wang; Jinjing Xiao; Haiqun Cao; Yanhong Shi (Journal of Hazardous Materials, 2024)

The association between per-/polyfluoroalkyl substances in serum and thyroid function parameters: A cross-sectional study on teenagers living near a Chinese fluorochemical industrial plant - Lin-Na Xie; Xiao-Chen Wang; Li-Qin Su; Sai-Sai Ji; Wen Gu; Holly Barrett; Xiao-Jie Dong; Hui-Juan Zhu; Sha-Sha Hou; Zhen-Huan Li; Yi-Lin Liu; Ling Zhang; et al. (Science of The Total Environment, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Identification a novel Ganoderma FIP gene from Ganoderma capense and its functional expression in Pichia pastoris - Jingwei Lin; Yating Liao; Sijia Yang; Taicheng Jin; Boning Yu; Kai Zhao; Yixiao Sai; Cheng Lin; Yanhua Song; Hui Ma; Zhanyong Wang (World Journal of Microbiology and Biotechnology, 2024)

Effect of N/P ratio on attached microalgae growth and the differentiated metabolism along the depth of biofilm - Weiyi Qian; Yanan Yang; Sai Chou; Shuhan Ge; Peihua Li; Xiaoxiong Wang; Lin-Lan Zhuang; Jian Zhang (Environmental Research, 2024)

Genetic variations of CYP3A4 on the metabolism of itraconazole in vitro - Sai-li Xie; Xiayan Zhu; Nanyong Gao; Qianmeng Lin; Chaojie Chen; Yun-jun Yang; Jian-ping Cai; Guo-xin Hu; Ren-ai Xu (Food and Chemical Toxicology, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

Sn2+/Mn2+ co-doped germanate glass with quasi-sunlight spectrum visible-emission and its high-quality w-LED application - Yuhang Zhang; Baojiu Chen; Xizhen Zhang; Yongze Cao; Jinsu Zhang; Sai Xu; Xiangping Li; Hongquan Yu; Duan Gao; Xuezhu Sha; Li Wang; Xin Chen; et al. (Chemical Engineering Journal, 2023)

Inpainting truncated areas of CT images based on generative adversarial networks with gated convolution for radiotherapy - Kai Xie; Liugang Gao; Heng Zhang; Sai Zhang; Qianyi Xi; Fan Zhang; Jiawei Sun; Tao Lin; Jianfeng Sui; Xinye Ni (Medical & Biological Engineering & Computing, 2023)

Multiple metal exposure and metabolic syndrome in elderly individuals: A case-control study in an active mining district, Northwest China - Sai Guo; Liting Hua; Wu Liu; Hongxiu Liu; Qiusheng Chen; Yongcheng Li; Xiaoxiao Li; Leicheng Zhao; Ruoqi Li; Zining Zhang; Chong Zhang; Lin Zhu; et al. (Chemosphere, 2023)

Effects of conservation agriculture on carbon mineralization: A global meta-analysis - Cong He; Zhe Chen; Ke-Yi Qiu; Jin-Sai Chen; Yves N'Dri Bohoussou; Yash Pal Dang; Hai-Lin Zhang (Soil and Tillage Research, 2023)

Developing a novel framework to re-examine half a century of compound drought and heatwave events in mainland China - Lin Zhao; Xinxin Li; Zhijiang Zhang; Moxi Yuan; Shao Sun; Sai Qu; Mengjie Hou; Dan Lu; Yajuan Zhou; Aiwen Lin (Science of The Total Environment, 2023)

Recent progress on highly efficient removal of heavy metals by layered double hydroxides - Tong He; Qian Li; Tong Lin; Jiaxin Li; Sha Bai; Sai An; Xianggui Kong; Yu-Fei Song (Chemical Engineering Journal, 2023)

Historical biomonitoring of pollution trends in the North Pacific using archived samples from the Continuous Plankton Recorder Survey - Kefeng Li; Jane C. Naviaux; Sai Sachin Lingampelly; Lin Wang; Jonathan M. Monk; Claire M. Taylor; Clare Ostle; Sonia Batten; Robert K. Naviaux (Science of The Total Environment, 2023)

Dispersal limitation and host selection drive geo-specific and plant-specific differentiation of soil bacterial communities in the Tibetan alpine ecosystem - Sai Qu; Congcong Shen; Lin Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (Science of The Total Environment, 2023)

Emulsifying properties and oil–water interface properties of succinylated soy protein isolate: Affected by conformational flexibility of the interfacial protein - Ziteng Lian; Sai Yang; Lin Cheng; Peilong Liao; Shicheng Dai; Xiaohong Tong; Tian Tian; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2023)

Decoupling analysis of China's mining industrial development and water usage: Based on production-based and consumption-based perspectives - Yiming Li; Yingnan Zhang; Lin Yang; Fenglian Du; Linna Sai; Bin Zhang (Journal of Cleaner Production, 2023)

The impact of clean energy development finance and financial agglomeration on carbon productivity in Africa - Rockson Sai; Boqiang Lin; Xiying Liu (Environmental Impact Assessment Review, 2023)

Administration of the Potential Probiotic Paenibacillus ehimensis NPUST1 Enhances Expression of Indicator Genes Associated with Nutrient Metabolism, Growth and Innate Immunity against Aeromonas hydrophila and Streptococcus indie Infections in Zebrafish (Danio rerio) - Pei-Hui Lin; Sai-Wei Chen; Zhi-Hong Wen; Shao-Yang Hu (Fishes, 2022)
Probiotics as antibiotic alternatives for preventing and controlling infectious diseases are a relatively eco-friendly strategy in aquaculture. The bacteriocin-producing probiotic Paenibacillus ehimensis NPUST1 was isolated from tilapia culture pond water in our previous study. The present study demonstrated that P. ehimensis NPUST1 produced hydrolytic enzymes, including protease, amylase, cellulase, xylanase and lipase. The effects of P. ehimensis NPUST1 on zebrafish nutrient metabolism, growth performance and innate immunity were evaluated by measuring the expression of indicator genes in zebrafish after feeding P. ehimensis NPUST1 at doses of 106 and 107 CFU/g for 8 weeks. There was an obvious increase in the hepatic mRNA expression of carbohydrate metabolism-related genes, including glucokinase, hexokinase 1, glucose-6-phosphatase, and pyruvate kinase, and growth-related genes, including the growth hormone receptor and insulin-like growth factor-1. The expression of the innate immune-related genes including interleukin (IL)-1β, IL-6, IL-15, tumor necrosis factor-α, toll-like receptor (TLR)-1, TLR-4, complement component C3b and lysozyme were significantly increased in P. ehimensis NPUST1-supplemented fish. A significant reduction in cumulative mortality was exhibited in P. ehimensis NPUST1-supplemented fish after infection with Aeromonas hydrophila and Streptococcus iniae. In conclusion, our data suggested that P. ehimensis NPUST1 supplementation in feed could potentially improve nutrient metabolism and growth in addition to enhancing innate immunity and disease resistance against A. hydrophila and S. iniae in zebrafish.

Alcanivorax limicola sp. nov., isolated from a soda alkali-saline soil - Lin Zhu; Yuan Wang; Yiwei Ding; Kai Luo; Biyue Yang; Sai Yang; Shenkui Liu; Henglin Cui; Wei Wei (Archives of Microbiology, 2022)

Geo-structures and deformation-failure characteristics of rockslide areas near the Baige landslide scar in the Jinsha River tectonic suture zone - Shi-lin Zhang; Yue-ping Yin; Xie-wen Hu; Wen-pei Wang; Zong-liang Li; Xin-ming Wu; Gang Luo; Sai-nan Zhu (Landslides, 2021)

Phytoactinopolyspora limicola sp. nov., an alkaliphilic actinomycete isolated from a soda alkali-saline soil - Wei Wei; Kaili Wang; Xinyu Hu; Sai Yang; Chunlin Zeng; Zhaozhi Hou; Shenkui Liu; Henglin Cui; Lin Zhu (Archives of Microbiology, 2021)

Initiation mechanism of the Baige landslide on the upper reaches of the Jinsha River, China - Shi-lin Zhang; Yue-ping Yin; Xie-wen Hu; Wen-pei Wang; Sai-nan Zhu; Nan Zhang; Shui-he Cao (Landslides, 2020)

Stable isotopes reveal effects of natural drivers and anthropogenic pressures on isotopic niches of invertebrate communities in a large subtropical river of China - Sai Wang; Lin-Hui Su; Bang-Ke Luo; Ying-Jun Qin; Simon D. Stewart; Jin-Peng Tang; Tuan-Tuan Wang; Yang Yang; Gong Cheng (Environmental Science and Pollution Research, 2020)

Anomalous winter moisture transport associated with the recent surface warming over the Barents–Kara seas region since the mid‐2000s - Sai Wang; Wen Chen; Shangfeng Chen; Debashis Nath; Lin Wang (International Journal of Climatology, 2020)
Observational evidences have shown that the increased water vapour and accompanying enhancement of downward infrared radiation (IR) can explain the abrupt warming of surface air temperature (SAT) over the Barents–Kara Seas during boreal winter. This study investigates anomalous moisture transport associated with the abrupt change of SAT since the mid‐2000s over the Barents–Kara Seas, since moisture transport contributes to the anomalous water vapour and downward IR. Results show that anomalous stationary moisture flux induces anomalous moisture convergence over the Barents–Kara Seas region, whereas the anomalous transient flux opposes the anomalous moisture convergence there. Hence, the anomalous stationary moisture transport is suggested to be responsible to the increased water vapour over the Barents–Kara Seas region. Further decomposition of the stationary moisture flux indicates that the anomalous moisture convergence associated with the change in atmospheric mean flow plays an important role in the increased water vapour on both interannual and decadal time scales. In addition, decrease in the synoptic‐scale eddy activity observed over northern Siberia may contribute to generation of the anomalous atmospheric mean flow via eddy feedback processes.

Changes in winter stationary wave activity during weak mid‐latitude and Arctic thermal contrast period - Sai Wang; Debashis Nath; Wen Chen; Lin Wang (International Journal of Climatology, 2020)
Using reanalysis data set, this study investigates the changes in winter mean stationary wave activity, when the thermal contrast between mid‐latitude and Arctic is weak. The mid‐latitude and Arctic thermal contrast was stronger during 1986–2003 and weaker during 1966–1985 and 2004–2017. The changes in stationary wave characteristics are studied based on the stationary wave activity flux (SWAF). Compare to the period when the contrast was stronger (1986–2003), both the convergence of SWAF and stationary wave amplitude have been enhanced in the Northern part of Eurasia during the periods 1966–1985 and 2004–2017. We further proposed that a weak mid‐latitude/Arctic thermal contrast provides a good condition for the enhancement of the stationary wave activity. The weak mid‐latitude‐Arctic thermal contrast is conducive to the enhancement of blocking frequency around Ural Mountains, which may contribute partly to the increase in stationary wave amplitude and associated changes in the SWAF. Furthermore, the weak thermal contrast is associated with the decrease in baroclinicity and synoptic‐scale eddy activity, which in turn contributes to the generation of stationary waves via eddy feedback processes.

Variations in land surface phenology and their response to climate change in Yangtze River basin during 1982–2015 - Moxi Yuan; Lunche Wang; Aiwen Lin; Zhengjia Liu; Sai Qu (Theoretical and Applied Climatology, 2019)

Fish feeding groups, food selectivity, and diet shifts associated with environmental factors and prey availability along a large subtropical river, China - Sai Wang; Jin-Peng Tang; Lin-Hui Su; Jing-Jing Fan; Hao-Yen Chang; Tuan-Tuan Wang; Lin Wang; Hsing-Juh Lin; Yang Yang (Aquatic Sciences, 2019)

Mechanistic studies of the apoptosis induced by the macrocyclic natural product tetrandrine in MGC 803 cells - Sai-Qi Wang; Hong-Lin Hou; Liang-Yu Bie; Cai-Yun Nie; Luo-Nan Wang; Shaobing Gao; Ting-Ting Hu; Xiao-Bing Chen (Medicinal Chemistry Research, 2019)

Promoters of Arabidopsis Casein kinase I-like 2 and 7 confer specific high-temperature response in anther - Yaoyao Li; Ling Min; Lin Zhang; Qin Hu; Yuanlong Wu; Jie Li; Sai Xie; Yizan Ma; Xianlong Zhang; Longfu Zhu (Plant Molecular Biology, 2018)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

The Interaction of Mitochondrial Biogenesis and Fission/Fusion Mediated by PGC-1α Regulates Rotenone-Induced Dopaminergic Neurotoxicity - Kaige Peng; Likui Yang; Jian Wang; Feng Ye; Guorong Dan; Yuanpeng Zhao; Ying Cai; Zhihong Cui; Lin Ao; Jinyi Liu; Zhongmin Zou; Yan Sai; et al. (Molecular Neurobiology, 2017)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

The effects of grafting on glycolysis and the tricarboxylic acid cycle in Ca(NO3)2-stressed cucumber seedlings with pumpkin as rootstock - Lin Li; Wen-wen Xing; Qiao-sai Shao; Sheng Shu; Jin Sun; Shi-rong Guo (Acta Physiologiae Plantarum, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Multiple Mesozoic magma processes formed the 240–185 Ma composite Weishan pluton, South China: evidence from geochronology, geochemistry, and Sr-Nd isotopes - Xing Ding; Wei-Dong Sun; Wei-Feng Chen; Pei-Rong Chen; Tao Sun; Sai-Jun Sun; Chiou-Ting Lin; Fu-Kun Chen (International Geology Review, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Comparison of fatty acid and amino acid profiles of steamed Chinese mitten crab - Yan-Ru Guo; Sai-Qi Gu; Xi-Chang Wang; Lin-Min Zhao; Jin-Yuan Zheng (Fisheries Science, 2014)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

An effective and simplified scale-up strategy for acarbose fermentation based on the carbon source control - Kun-tai Li; Sai-jin Wie; Lin Huang; Xin Cheng (World Journal of Microbiology and Biotechnology, 2012)

Genetic similarity among cultivars of Phyllostachys pubescens - Xin Chun Lin; Xiao Sai Ruan; Yong Feng Lou; Xiao Qin Guo; Wei Fang (Plant Systematics and Evolution, 2009)

A new distribution record for Trigonobalanus verticillata (Fagaceae) from Hainan Island, South China - Sai-Chit Ng; Jia-Yi Lin (Kew Bulletin, 2008)

Timing of UHP metamorphism in the Hong’an area, western Dabie Mountains, China: evidence from zircon U–Pb age, trace element and Hf isotope composition - Yuan-Bao Wu; Shan Gao; Hong-Fei Zhang; Sai-Hong Yang; Wen-Fang Jiao; Yong-Sheng Liu; Hong-Lin Yuan (Contributions to Mineralogy and Petrology, 2007)